Sistem Informasi Arsip Pada Lembaga Kursus Dan Pelatihan Intermedia Training Center Labuhanbatu Berbasis Web - Fadilla, Rizki (Universitas Labuhanbatu, 2021)
The writing of this Final Project aims to design an Information System. This system is expected to facilitate the archive of incoming and outgoing letters. As well as one of the requirements to take the Examination Trial Final Tests At Computer Information Management Academy (AMIK) Labuhan Batu. The programming language used in making the System in question is Using PHP and MySQL. Database Creation Application using MySQL and ServerAppserv, Localhost Phpmyadmin. Preparation of this Final Project begins by formulating the problem, Identifying problems, Determination of Objectives and Benefits and Collecting data on the History of the establishment of the Agency. After all the data needed in get, then proceed to Process System Analysis. After all the data needed is obtained, then proceed to prosea system analysis. The result of making a program that is intended with the completion of we-based archive information system. Hopefully with this information system can improve performance in the process of storing and searching data for incoming and outgoing letters on LKP. Intermedia Training Center Labuhanbatu.